Effect of insulin resistance on gonadotropin and bone mineral density in nondiabetic postmenopausal women - Ye, Shujin; Shi, Lan; Zhang, Zhifen (Frontiers in Endocrinology, 2023)
Objective: The effects of insulin resistance (IR) on bone mineral density (BMD) are unclear. This investigation aimed to assess the impact of IR and hyperinsulinemia on bone health. Determine whether IR mediates the link between follicle-stimulating hormone (FSH) and bone mass in nondiabetic postmenopausal women. Design: Retrospective cross-sectional study Setting: Health checkup center of Hangzhou Women's Hospital. Methods: This study comprised 437 nondiabetic postmenopausal women. BMD was evaluated using dual-energy X-rays. Fasting sera were analyzed for insulin and glucose levels, and indicators related to IR were determined. By pathway analysis, we examined the indirect effects of FSH on BMD via the mediators Homeostatic Model Assessment for insulin resistance (HOMA-IR) and fasting insulin (FINS) after correction for confounding factors. Result: After adjusting for age and body mass index (BMI) in linear regression, HOMA-IR and FINS were linked with FSH (P<0.05). IR was stronger among women in the normal BMD group than those in the osteoporosis or osteopenia group. In unadjusted models, BMD was greater in those with higher HOMA-IR and FINS (β=0.027, P=0.006 and β=0.033, P=0.003, respectively). After correcting for BMI and other possible variables, these associations remained. In addition, path models for FSH demonstrated a negative association with BMD by HOMA-IR (95% confidence interval [CI]: -0.0174 to -0.0014) and FINS (95% CI: -0.0188 to -0.002). Conclusion: Greater IR was associated with increased BMD in nondiabetic postmenopausal women, regardless of BMI and other variables. HOMA-IR or FINS could play a novel mediating role in FSH-induced BMD suppression.